The crucial roles of inflammatory mediators in inflammation: a review - Abdulkhaleq, Layth Abdulmajeed; Assi, Mohammed Abdulrazzaq; Abdullah, Rasedee; Saad, M. Zamri; Mohd Noor, Mohd Hezmee; Yap, Taufiq Yun Hin (Veterinary World, 2018)
The inflammatory response is a crucial aspect of the tissues’ responses to deleterious inflammogens. This complex response involves leukocytes cells such as macrophages, neutrophils, and lymphocytes, also known as inflammatory cells. In response to the inflammatory process, these cells release specialized substances which include vasoactive amines and peptides, eicosanoids, proinflammatory cytokines, and acute-phase proteins, which mediate the inflammatory process by preventing further tissue damage and ultimately resulting in healing and restoration of tissue function. This review discusses the role of the inflammatory cells as well as their by-products in the mediation of inflammatory process. A brief insight into the role of natural anti-inflammatory agents is also discussed. The significance of this study is to explore further and understand the potential mechanism of inflammatory processes to take full advantage of vast and advanced anti-inflammatory therapies. This review aimed to reemphasize the importance on the knowledge of inflammatory processes with the addition of newest and current issues pertaining to this phenomenon.